NAVIGATING THE DIGITAL FRONTIER: A COMPREHENSIVE ANALYSIS OF DIGITAL TAXATION AND ITS IMPLICATIONS ON GLOBAL ECONOMICSTABILITY - Kevin Hermanto Tupamahu; Agung Cucu Purnawirawan; Mohammad Taqiuddin Mohamad (Adisam Publisher, 2024)
The rapid evolution of the digital economy has reshaped global commerce, introducing unprecedented opportunities and complexities in taxation and economic equilibrium. This paper presents a comprehensive systemic risk analysis to scrutinize the intricate interplay between digital taxation and the stability of the global economy. Through an exhaustive review of literature, case studies, and empirical data, it identifies and explores critical taxation challenges inherent in the digital realm, including tax base erosion, jurisdictional ambiguity, and regulatory fragmentation. Additionally, the analysis delves into the systemic risks associated with digital taxation, such as double taxation, tax competition, trade disputes, and regulatory arbitrage, emphasizing their far-reaching implications on economic stability, investment decisions, market dynamics, and fiscal sustainability. Drawing insights from effective mitigation strategies and successful case studies, the paper offers actionable recommendations for policymakers. These recommendations advocate for enhanced international cooperation, the development of consensus- based taxation frameworks, the utilization of digital technologies for tax compliance, and the reinforcement of multilateral institutions. By proactively addressing systemic risks, policymakers can nurture economic stability, spur innovation, and establish a fair and equitable tax landscape amidst the complexities of the digital era. This analysis contributes significantly to the ongoing discourse on digital taxation, providing valuable guidance for policymakers, researchers, and practitioners navigating the digital landscape while safeguarding global economic stability.